Influence of Classical Massage on Biochemical Markers of Oxidative Stress in Humans: Pilot Study. (10th December 2021) - Skubisz, Zofia; Kupczyk, Daria; Goch, Aleksander; Siedlaczek, Marcin; Sielski, Łukasz; Niespodziński, Bartłomiej; Mikołajewska, Emilia; Zasada, Mariusz; Augustyńska, Beata
Abstract : Classical massage is one of the most popular forms of conservative treatment in various diseases. Despite the wide scope of research, the mechanisms of massage are not fully known and understood. Apart from the well-described effects on individual body systems, there are few scientific reports on the effects of massage on the human body at the subcellular level. The study was designed to assess changes in oxidative stress parameters in healthy volunteers after a single session of classical massage. 29 healthy volunteers aged 22.24 ± 3.64 participated in the study. Before and 30 minutes after the massage procedures, blood samples were taken by experienced personnel. Biochemical markers of oxidative homeostasis were assessed with highly specific methods for each parameter: oxidase ceruloplasmin, glutathione, malondialdehyde, glutathione peroxidase, glutathione S-transferase, and superoxide dismutase. The study demonstrates that massage therapy caused statistically significant decrease in the concentration of glutathione peroxidase (red blood cells) and increase in the level of glutathione peroxidase (plasma), superoxide dismutase, and malondialdehyde. In contrast, statistically significant changes in the hematocrit, glutathione, NO2- /NO3-, and oxidase ceruloplasmin were not observed. The results show that complex influence of classical massage therapy on human organism may be reflected in parameters of the oxidative stress. To understand this mechanism clearly, further research is needed.